The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/aps.2013.203
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin prevents amyloid-β peptide oligomer-induced synaptotoxicity and memory dysfunction in rats through a p38 MAPK-dependent pathway

Abstract: Aim: To investigate whether atorvastatin treatment could prevent Aβ 1-42 oligomer (AβO)-induced synaptotoxicity and memory dysfunction in rats, and to elucidate the mechanisms involved in the neuroprotective actions of atorvastatin. Methods: SD rats were injected with AβOs (5 nmol, icv). The rats were administrated with atorvastatin (10 mg·kg -1 ·d -1 , po) for 2 consecutive weeks (the first dose was given 5 d before AβOs injection). The memory impairments were evaluated with Morris water maze task. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 63 publications
2
36
0
Order By: Relevance
“…AβOs were prepared from Aβ . This preparation contains a mixture of AβOs plus some monomers [17] . We assessed the effects of atorvastatin on hippocampal neurons that were acutely exposed to AβOs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…AβOs were prepared from Aβ . This preparation contains a mixture of AβOs plus some monomers [17] . We assessed the effects of atorvastatin on hippocampal neurons that were acutely exposed to AβOs.…”
Section: Discussionmentioning
confidence: 99%
“…Clarke et al demonstrated that rats treated with atorvastatin for 3 weeks were protected against a deficiency in LTP caused by the acute injection of Aβ 1-42 [20] . Our previous results revealed that atorvastatin prevented AβO-induced synaptotoxicity, which leads to memory dysfunction through a p38MAPK-dependent pathway [17] . However, the mechanisms underlying the neuroprotective effects of statins have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Western blot analysis was performed as previously described [29] . Whole cell lysates were prepared from A549 cells or BEAS-2B cells cultured in 6-well dishes using radioim-www.chinaphar.com Fu T et al Acta Pharmacologica Sinica npg munoprecipitation assay (RIPA) lysis buffer in the presence of protease inhibitors.…”
Section: Western Blotting Analysismentioning
confidence: 99%